Analisis Pengaruh dan Efisiensi Ekonomi Usahatani Padi Sawah di Rimbo Kedui, Seluma, Bengkulu - Nofitasari, Rahmi; Sihombing, Vista Uli; Siahaan, Herlyna Novasari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Rice plants are cultivated in more than 100 countries in the world, of which 90% are grown on the Asian continent in the Southeast Asia region. The land area of 152 million hectares produces around 600 million tons annually. The majority of farmers in Rimbo Kedui Village, Seluma Regency, Bengkulu Province work as lowland rice farmers. This research wants to analyze farming efficiency based on land area. Apart from that, this research wants to analyze the influence of land area on income and production of lowland rice farming in Rimbo Kedui Village, Seluma, Bengkulu. The number of samples in this study was 68 people. The research was carried out in Rimbo Kedui Village, West Seluma District, Seluma Regency, Bengkulu Province. Election of Rimbo Kedui Subdistrict. The population in this study were farmers in Rimbo Kedui Village, Seluma Barat District. Data analysis uses income and efficiency analysis, as well as using multiple linear regression data analysis. The results of efficiency calculations show that lowland rice farming with a small land area and a large land area is 1.92 and 181. So lowland rice farming with a small land area with a size of less than 0.5 Ha is more efficient than farming with a land area of more than 0.5 Ha. Based on a simple linear regression test, it shows that land area influences income and production of lowland rice farming. So the larger the land area, the greater the farmer's income and production.